ANALYSIS OF PUBLIC ADMINISTRATION DIGITALIZATION IN INDONESIA AND SOUTH KOREA - Saputro, Rio Asmoro; Aminullah (International Journal of Multidisciplinary Reseach, 2025)
The rapid advancement of digital technology has triggered profound transformations in public administration systems across the world. Public administration digitalization is no longer understood merely as the application of information technology to public services, but rather as a comprehensive bureaucratic reform encompassing changes in administrative processes, service delivery mechanisms, institutional coordination, and the relationship between government and citizens. Digitalization has become a strategic instrument to enhance governmental effectiveness, efficiency, transparency, and accountability, while simultaneously improving the overall quality of public services. Indonesia and South Korea are two countries that have actively adopted public administration digitalization policies, yet they demonstrate different levels of maturity, readiness, and achievement. This study aims to analyze and compare the implementation of public administration digitalization in Indonesia and South Korea by focusing on policy frameworks, digital infrastructure development, service integration, and the capacity of public sector human resources. This research employs a qualitative descriptive method with a comparative approach. Data were collected through literature review and document analysis, drawing from national and international academic journals, reports from international organizations, and official government publications from both Indonesia and South Korea. Data analysis was conducted through systematic stages of data reduction, data presentation, and conclusion drawing. The findings indicate that South Korea has achieved a more advanced level of public administration digitalization than Indonesia, particularly in terms of integrated digital public services, equitable digital infrastructure development, and highly competent public sector human resources. In contrast, Indonesia continues to face significant challenges, including regional digital disparities, weak inter-agency coordination, limited system integration, and constrained bureaucratic capacity in managing digital transformation. This study is expected to contribute to policy evaluation and provide strategic references for strengthening public administration digitalization in Indonesia.